The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1139/b00-002
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the taxonomic position of the African genus Colletoecema (Rubiaceae): morphology and anatomy compared to an rps16-intron analysis of the Rubioideae

Abstract: The morphology and anatomy of the African monospecific genus Colletoecema E. Petit (Rubiaceae) is documented and illustrated (including wood anatomy, pollen morphology, gynoecial and exotestal structure). Morphological and anatomical comparison shows that Colletoecema differs in many aspects from the Psychotrieae (e.g., wood anatomy, seed structure). Consequently, the genus' provisional position in the Psychotrieae cannot be maintained. Morindeae, the second tribe Colletoecema has been associated with, has a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…in agreement with the results of robbrecht & Manen (2006) andrydin et al (2008), Colletoecema is sister to all other rubioideae in our Bayesian analysis, but without support (bs < 50; PP = 0.86). This result also confirms the finding of Piesschaert et al (2000) based on rps16 intron sequences that Colletoecema does not belong to Morindeae (Petit 1963) or Psychotrieae (robbrecht 1993). However, a relationship between Colletoecema and Ophiorrhiza, as inferred with weak support by Piesschaert et al (2000), is not sup-ported here.…”
Section: Relationships Among Basal Rubioideaesupporting
confidence: 88%
See 2 more Smart Citations
“…in agreement with the results of robbrecht & Manen (2006) andrydin et al (2008), Colletoecema is sister to all other rubioideae in our Bayesian analysis, but without support (bs < 50; PP = 0.86). This result also confirms the finding of Piesschaert et al (2000) based on rps16 intron sequences that Colletoecema does not belong to Morindeae (Petit 1963) or Psychotrieae (robbrecht 1993). However, a relationship between Colletoecema and Ophiorrhiza, as inferred with weak support by Piesschaert et al (2000), is not sup-ported here.…”
Section: Relationships Among Basal Rubioideaesupporting
confidence: 88%
“…in addition the leaves of C. magna are larger and more distinctly obovate than observed in C. dewevrei and the fruits are also sessile and more than double in size. Also pollen is slightly different: grains of C. dewevrei are described as exclusively 3-colporate (Piesschaert et al 2000), while in C. magna both 3-and 4-colporate pollen grains were observed. This kind of pollen variation is not uncommon in Rubiaceae.…”
Section: Diagnostic Characters and Relationshipsmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, Xiao & Zhu's (2007) results are compatible with those of Andersson & Rova (1999). Piesschaert et al (2000) added seven more genera of Rubioideae to the morphological and molecular matrix and following their cladistic analysis Lasianthus, Saldinia and Trichostachys form a closely related group and Perama is more distantly related to this group. Piesschaert et al (2000) also found additional morphological and anatomical characters to support Petit's (1964) ideas on the tribal characters of the Psychotrieae and Morindeae.…”
Section: The Position In Rubiaceaementioning
confidence: 69%
“…Piesschaert et al (2000) added seven more genera of Rubioideae to the morphological and molecular matrix and following their cladistic analysis Lasianthus, Saldinia and Trichostachys form a closely related group and Perama is more distantly related to this group. Piesschaert et al (2000) also found additional morphological and anatomical characters to support Petit's (1964) ideas on the tribal characters of the Psychotrieae and Morindeae. The Psychotrieae mostly have terminal inflorescences, wood with radial multiple vessels, and seeds with small embryos and horny (not oily) endosperm.…”
Section: The Position In Rubiaceaementioning
confidence: 99%